Death on the Tiber - Davis, Lindsey (Davis, Lindsey. Flavia Albia mystery, 2024)
"In first century Rome, a murder victim found in the Tiber leads to a brutal gang war and Flavia Albia to a confrontation with her long-hated nemesis, with all that she loves in the balance. First century Rome is plagued by all the evils the have beset major cities since time immemorial: crime, corruption, squalor, and worst of all, tourists. When a barge full of those entitled creatures arrives in Rome, they hit all the touristy hot-spots (the Amphitheatre, the Capitol, the dodgy bars with dubious entertainments) before departing for the next destination--leaving behind one of their party, dead and floating in the Tiber. While the authorities first try to pass her death off as a suicide, it's quickly proved that the victim strangled to death and her body dumped. When Flavia Albia, a private informer, learns that the victim was in Rome searching for the man who abandoned her, Florius, Albia's vicious nemesis, Albia is determined to find out the truth behind the murder and finally have her revenge. Florius is the husband of the leader of the Balbinus, one of Rome's most vicious criminal gangs, giving him even more reason to have murdered his former mistress. Currently engaged in a brutal turf war, with bodies dropping everywhere, Florius is fighting for his very survival and has little interest in one dead body. Now Albia must risk everything, including the life she has carefully built, if she is finally to bring Florius to justice. If justice is even possible"--